2012
DOI: 10.1186/1476-7120-10-11
|View full text |Cite
|
Sign up to set email alerts
|

Could successful cryoballoon ablation of paroxysmal atrial fibrillation prevent progressive left atrial remodeling?

Abstract: BackgroundRadiofrequency catheter ablation of atrial fibrillation (AF) has been proved to be effective and to prevent progressive left atrial (LA) remodeling. Cryoballoon catheter ablation (CCA), using a different energy source, was developed to simplify the ablation procedure. Our hypothesis was that successful CCA can also prevent progressive LA remodeling.Methods36 patients selected for their first CCA because of nonvalvular paroxysmal AF had echocardiography before and 3, 6 and 12 months after CCA. LA diam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 39 publications
0
14
1
1
Order By: Relevance
“…Contrarily, among patients with AF recurrence, both structural and electrical remodeling showed a non-significant change during follow-up period. However, the study by Erdei et al [7] have significant difference from our study. First, they included patients with various risk factors for LA remodeling such as hypertension and coronary artery disease.…”
Section: Discussioncontrasting
confidence: 55%
See 3 more Smart Citations
“…Contrarily, among patients with AF recurrence, both structural and electrical remodeling showed a non-significant change during follow-up period. However, the study by Erdei et al [7] have significant difference from our study. First, they included patients with various risk factors for LA remodeling such as hypertension and coronary artery disease.…”
Section: Discussioncontrasting
confidence: 55%
“…Second, the recurrence rate was importantly high at 12-month follow-up (58 %) in the study by Erdei et al [7] as compared to lower recurrence rate in our study (21.9 %). Third, the study group of Erdei et al [7] revealed a higher LA dimensions (55±5 mm) which implies the preprocedural progressive structural remodeling and makes reverse remodeling more difficult. However, in our study, we excluded patients with LA diameter of >55 mm which prevents the inclusion of patients with probably irreversible LA remodeling.…”
Section: Discussionmentioning
confidence: 42%
See 2 more Smart Citations
“…Немногочисленные исследования по изучению влияния криобаллонной изоляции ЛВ на функцию ЛП демонстрируют, что в случае неуспеха процедуры имеет место прогрессирующее ухудшение механиче-ской функции, в то же время, при отсутствии рециди-вов ФП с шестого месяца после вмешательства име-ется тенденция к ее восстановлению [17,18]. Эти данные согласуются с результатами мета-анализа по оценке функции ЛП после РЧ изоляции ЛВ [9].…”
unclassified